The Rhox5 Homeobox Gene Regulates the Region-Specific Expression of Its Paralogs in the Rodent Epididymis - MacLean, James A. (Society for the Study of Reproduction, Inc., 2012)
The mechanisms by which the region-specific expression patterns of clustered genes evolve are poorly understood. The epididymis is an ideal organ to examine this, as it is a highly segmented tissue that differs significantly in structure between closely related species. Here we examined this issue through analysis of the rapidly evolving X-linked reproductive homeobox (Rhox) gene cluster, the largest known homeobox gene cluster in metazoans. In the mouse, we found that most Rhox genes are expressed primarily in the caput region of the epididymis, a site where sperm mature and begin acquiring forward motility. This region-specific expression pattern depends, in part, on the founding member of the Rhox cluster—Rhox5—as targeted mutation of Rhox5 greatly diminishes the expression of several other family members in the caput region. In the rat, Rhox5 expression switches from the caput to the site of sperm storage: the cauda. All Rhox genes under the control of Rhox5 in the mouse epididymis display a concomitant change in their regional expression in the rat epididymis. Our results lead us to propose that widespread changes in the region-specific expression pattern of genes over evolutionary time can be the result of alterations of one or only a few master regulatory genes.